Evaluasi Kegagalan Sistem Mitigasi Tsunami: Studi Kasus Tohoku 2011 - Tri Ayu Lestari (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
The 2011 Tohoku tsunami stands as one of the most catastrophic natural disasters in Japan’s history, resulting in massive loss of life, extensive property damage, and severe disruption to infrastructure along the northeastern coast. This study aims to examine the physical characteristics of the Tohoku tsunami and critically evaluate the factors that led to the failure of Japan’s disaster mitigation systems. Utilizing an essay-based synthesis approach, this analysis draws from a range of previous research findings and post-disaster assessments. The tsunami was caused by a 9.0 magnitude megathrust earthquake off the eastern coast of Honshu, generating wave heights that exceeded 10 meters in several locations. The tsunami’s immense energy produced destructive currents that penetrated deep inland, surpassing the protection capabilities of existing coastal defenses.The study identifies several contributing factors to the mitigation system’s shortcomings: the design limitations of seawalls, which were not built to withstand such extreme events; delays and limitations in the early warning system’s ability to reach all at-risk populations in time; and inadequate public preparedness, as the event exceeded historical precedents and training scenarios. These vulnerabilities highlight the need for integrated, adaptive disaster risk management strategies.Drawing lessons from Japan’s experience, this study proposes recommendations for improving tsunami mitigation efforts in Indonesia. Key suggestions include reinforcing and redesigning coastal defense structures, advancing early warning technologies such as seabed sensors and coastal radar systems, and enhancing disaster literacy through public education and scenario-based training. By adopting a science- and technology-driven approach, Indonesia can strengthen its resilience and reduce vulnerability among coastal populations facing future tsunami threats.